Pendidikan Nilai Karakter Menurut KH Hasyim Asy’ari dan Imam Ghazali - Nailil Maghfiroh; Muh. Nursikhin (CV. Ulil Albab Corp, 2022)
The purpose of this research is to know the value of character education according to the perspective of KH Hasyim Asy'ari and Imam Ghazali. This research used library research for its method, which is taking data related to the theme of the discussion from books, e-books, journals, articles, and literature sources, which are then analyzed to obtain data that related to the research objectives. The results of this study are several main points about character education according to the two figures, there are; religious, tolerance, discipline and hard work, as well as being honest, creative and caring for the environment which is in line with the goals of national education or sisdiknas.